Technology and innovation management in higher education-cases from Latin America and Europe - Antonio Adrián Arciénaga Morales; Janni Nielsen; Hernán Alberto Bacarini; Silvia Irene Martinelli; Sergio Takeo Kofuji; Juan Francisco García Díaz (Administrative Sciences, 2018)
To solve common bottlenecks in the innovation and development process known as the 'European Paradox' or the 'Latin American Innovative Gap', we introduce different experiences of training and education at graduate level. The main objective of this study is to analyze different cases from Europe and Latin America to synthetize a model of technology and innovation management. Conceptually, the model focuses on competences, tools, skills and behaviors. From this knowledge base, we derive a new model of learning for higher education, using an organizational framework. Our model of learning includes different ways to obtain a panoply of competencies to identify technology and innovation management issues at individual business and regional level, particularly for small-and-medium-sized enterprises (SMEs). The model addresses innovation challenges related to new innovative relationships and product opportunities emerging from traditional sectors, but also from nanotechnology, biotech and ICT fields, with particular emphasis on environmental and sustainability problems. We suggest that our two models may serve as the foundation for designing a curricular master's program for higher education, in accordance with the Latin American and European realities.
Keywords: 350; innovation management tools; innovation capabilities; technological innovation; university-company interaction; learning model; higher education